The Relationship Between Feeding Patterns and Stunting Incidence in Toddlers from the Perspective of Maqashid Shariah - Saputri, Weni; Irwansyah, Irwansyah (Newinera Publisher, 2025)
Stunting is a condition where a person's height is shorter than the height of other people in general. Stunting is a condition of failure to thrive in children under five as a result of chronic malnutrition so that the child is too short for his age. Factors that cause stunting include food intake, infectious diseases, parenting patterns, health services and environmental sanitation, economic, socio-cultural, educational and environmental factors. The research aims to determine the relationship between feeding patterns and the incidence of stunting among toddlers in the Working Area of the Terjun Community Health Center, Medan Marelan District. The research was carried out from March to August 2024 in the Working Area of the Terjun Community Health Center, Medan Marelan District using a cross sectional approach. The research sample was 100 respondents, taken using purposive sampling technique. The research results showed that 35.0% of toddlers were in the stunting category and 65.0% of toddlers were in the non-stunting category. The feeding pattern of toddlers is 54.0% of toddlers with inappropriate feeding patterns and 46.0% of toddlers with appropriate feeding patterns. The results of the chi-square test analysis of this research showed that there was a significant relationship between feeding patterns and the incidence of stunting in toddlers in the Working Area of the Terjun Community Health Center, Medan Marelan District with a significance value of p=0.009 (p<0.05), from the results of the analysis it was obtained also OR=6.756.